Penerapan Konseling Individu Mengunakan Teknik Reinforcement Positif dalam Mengatasi Perilaku Agresif (Studi Kasus pada Klien “I” di Desa Letang Kecamatan Babat Supat): Penelitian - Lisa Ayu Padila; Suryati; Hartika Utami Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the application of individual counseling using positive reinforcement techniques in overcoming aggressive behavior and the factors causing aggressive behavior in client "I". This qualitative study uses a case study method. Data collection techniques involve observation, interviews, and documentation. Data analysis used in this study is pattern matching, data explanation, and time series analysis. The results of the study show that individual counseling with positive reinforcement techniques in overcoming aggressive behavior in client "I" found that the client had difficulty in managing emotions and showed aggressive behavior, such as shouting, pushing, even hitting friends when feeling offended or not understood. Positive reinforcement techniques can strengthen positive behavior by providing reinforcement when the client shows a response or behavior that matches expectations. Intervention results showed that reinforcement techniques helped client "I" overcome aggressive behavior, improve communication, and build healthier social relationships with peers. This study recommends the use of reinforcement techniques as an effective approach to addressing aggressive behavior in individuals and providing benefits for counselors and related parties.